2019
DOI: 10.1097/pq9.0000000000000162
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Pressure Ulcers in a Pediatric Cardiac Intensive Care Unit

Abstract: Background: Pressure ulcer (PU) is an injury to skin or underlying tissue as a result of pressure or pressure with shear stress. We classify PUs by the level of tissue injury: stage I–IV, unstageable, suspected deep tissue injury. This quality project was aimed to reduce the incidence of PUs > stage II in the cardiothoracic intensive care unit. Methods: We reviewed PUs > stage II from March 2010 to December 2017. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 15 publications
0
32
0
1
Order By: Relevance
“…A study carried out in a Pediatric Cardiac Intensive Care Unit implemented interventions to reduce the pressure ulcer (PU) rates, such as a package of measures, multidisciplinary meetings, multidisciplinary weekly rounds, unit-specific work group and a form for recording information about the cause and prevention of each PU. The results of the study showed a reduction in the incidence of PU from 15.7 to 2.9 events per 1,000 patient-days, a reduction in the PUs related to immobility from 35 to 4, and a reduction in the PUs related to medical devices from 34 to 15 events 30 .…”
Section: /13mentioning
confidence: 91%
See 1 more Smart Citation
“…A study carried out in a Pediatric Cardiac Intensive Care Unit implemented interventions to reduce the pressure ulcer (PU) rates, such as a package of measures, multidisciplinary meetings, multidisciplinary weekly rounds, unit-specific work group and a form for recording information about the cause and prevention of each PU. The results of the study showed a reduction in the incidence of PU from 15.7 to 2.9 events per 1,000 patient-days, a reduction in the PUs related to immobility from 35 to 4, and a reduction in the PUs related to medical devices from 34 to 15 events 30 .…”
Section: /13mentioning
confidence: 91%
“…The use of support surfaces for pressure redistribution such as mattresses, cushions and pillows, as well as to protect bony prominences, helps to reduce the risk and incidence of pressure ulcers in critically-ill patients at high risk for their development, as well as the implementation of prevention protocols to promoting improvements in care quality [29][30] .…”
Section: /13mentioning
confidence: 99%
“…In dieser Gruppe dominieren die männlichen Patienten im Verhältnis von 3 : 1 [2]. Jedoch können auch bei kindlichen Patienten Druckulzera auftreten, wobei es sich zumeist um intensivmedizinisch therapierte Kinder handelt [3].…”
Section: Epidemiologieunclassified
“…Pressure ulcer (PU) is an injury to skin or underlying tissue as a result of pressure or pressure with shear stress [1]. Pressure ulcer is localized damage to the skin or underlying soft tissue, usually over a bony prominence or related to a medical device or other equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, children at greatest risk are those requiring mechanical ventilation or inotropic support; those who suffer a cardiac arrest following cardiac surgery; those with nutritional deficits and children with longer hospital lengths of stay. Medical device-associated pressure ulcers are frequent among pediatric patients with reported prevalence rates ranging from 50% to 69% [1].…”
Section: Introductionmentioning
confidence: 99%